2021
DOI: 10.1111/acel.13290
|View full text |Cite
|
Sign up to set email alerts
|

Protein signatures of centenarians and their offspring suggest centenarians age slower than other humans

Abstract: Using samples from the New England Centenarian Study (NECS), we sought to characterize the serum proteome of 77 centenarians, 82 centenarians' offspring, and 65 age‐matched controls of the offspring (mean ages: 105, 80, and 79 years). We identified 1312 proteins that significantly differ between centenarians and their offspring and controls (FDR < 1%), and two different protein signatures that predict longer survival in centenarians and in younger people. By comparing the centenarian signature with 2 independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 65 publications
3
47
0
Order By: Relevance
“…Current research mainly focuses on European populations and the sick older [ 13 – 16 ], with a lack of studies on Asian populations and community older. Centenarians, as the “template population” of population aging, have reference value for the extension of their life span and health to the general older population [ 17 ]. The longevity of centenarians in China’s Hainan Province is closer to natural longevity than that of those in areas with higher level of economic and medical.…”
Section: Introductionmentioning
confidence: 99%
“…Current research mainly focuses on European populations and the sick older [ 13 – 16 ], with a lack of studies on Asian populations and community older. Centenarians, as the “template population” of population aging, have reference value for the extension of their life span and health to the general older population [ 17 ]. The longevity of centenarians in China’s Hainan Province is closer to natural longevity than that of those in areas with higher level of economic and medical.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the overexpression of Pex5 has been shown to restore peroxisomal import function and preserve cardiac health in aged oenocytes [ 14 ]. Importantly, Sebastiani et al [ 169 ] studied the proteomic signatures of centenarians and identified that proteins encoding components of peroxisomes were significantly downregulated in centenarians’ serum compared with younger individuals. In addition, the bile acid metabolism pathway and cholesterol homeostasis pathway were also downregulated in centenarians.…”
Section: Peroxisomal Dysfunction In Aging and Aging-related Diseasesmentioning
confidence: 99%
“…In response to mitochondrial dysfunction, growth differentiation factor 15 (GDF15) may be generated, protecting tissues against inflammation by suppressing T-cell activation and mediating release of cytokines (Moon et al, 2020). On this basis, GDF15 was suggested as a potential aging biomarker (Justice et al, 2018;Tanaka et al, 2018;Basisty et al, 2020;Sebastiani et al, 2021). TGF-β and GDF11 (from the same protein superfamily) are also regarded as proteins playing a role in aging-associated cellular senescence, frailty, stem cell aging and fibrosis as well as surgical risk in older adults (Schafer et al, 2016;Khan et al, 2017;Niedernhofer et al, 2017;Bai, 2018;Dodig et al, 2019;Tominaga and Suzuki, 2019).…”
Section: Non-epigenetic Research Laboratory Biomarkersmentioning
confidence: 99%